(untitled) (International Journal of Biotechnology for Wellness Industries, 2013)
The aim of this work is to evaluate the effects of electrical stunning parameters of turkey on the quality of steak and stew using the response surface methodology. 1584 turkeys were used for the study. The parameters tested were the voltage and pulse. The responses were the sensory quality of steak and stew. The rejection rate varies between 0.23% (steak female) and 56.06% (female stew). Results show that it is possible to obtain a low rejection rates (< 1% for the steak of male turkey) at a voltage of 50 Volts and pulse of 7. In comparison of pulse, voltage remains the most important factor. The optimal conditions selected for the total output of the process obtained from the analysis of the response surfaces are: voltage, from 45 to 47 Volts; pulse from 6.5 to 7 and voltage from 50 to 52 Volts; pulse from 6.8 to 7, respectively for female and male turkeys. Under these experimental conditions, the rejection rates range from 0.23% to 0.80% and from 11.93% to 13.27% respectively for steak and stew. The results show that the voltage and pulse are both the parameters meaning on the global quality of steak and stew.